Kegiatan Sosialisasi Penyakit Lepra dalam Upaya Menurunkan Kasus Kejadian Lepra di Wilayah Kerja Puskesmas Kresek, Kecamatan Kresek, Kabupaten Tangerang, Provinsi Banten - Althaf Putri Hidayatullah; Dewi Indah Lestari (Lembaga Pengembangan Kinerja Dosen, 2026)
Leprosy is a neglected tropical disease with more than 200,000 new cases annually. Indonesia ranks third with the most cases. The Banten Provincial Health Office recorded 7 new cases of leprosy in June 2024. Early diagnosis and immediate treatment can prevent disability, and early detection and prevention can break the chain of transmission. This study aimed to reduce the number of new cases and carry out leprosy prevention efforts in Puskesmas Kresek area, Kresek District, Tangerang Regency, Banten Province. The method of this social activity used an active participatory and health education approach that involve the active participation of activity participants. The activity stages include coordination with stakeholders, knowledge surveys, development of socialization materials, provision of socialization materials, and activity evaluation. Based on the results of the activity, it shows a significant increase in participant knowledge (p value <0.05) as examined by the post-test results, namely, 24 (92.30%) of 26 participants and the screening results found one new case of leprosy. Lifestyle factors are the main cause of the increase in new cases of leprosy in the Puskesmas Kresek area. Therefore, this social activity is expected to increase public knowledge about leprosy and how to prevent it, thereby breaking the chain of transmission and reducing the number of new leprosy cases.